Monitoring the Open Access Policy Compliance at Malmö University - Andersson, Jacob (Septentrio Conference Series, 2014)
Malmö University implemented an open access policy in 2011. It states that research staff and postgraduate students at Malmö University must deposit a copy of their research publications in the university's open repository Malmö University Electronic Publishing (MUEP), a DSpace installation, unless copyright prevents this. It is our ambition that our researchers will investigate their open access rights for each of their publications, regardless of publication type. In late 2012 we made changes in the submission interface of the repository in order to improve the support given to the researchers regarding copyright issues. With these changes we also made it easier to monitor the compliance with the open access policy. The submission process now asks two new questions. The first of these require the author/submitter to state either that she is aware of her rights to deposit a copy of the publication in an open institutional repository, or ask for assistance. The second question is if the author has the right to make this deposit, or if assistance to interpret the agreement is needed. These mandatory questions have made it easier for our librarian specialized in legal issues to detect where support is needed. Hopefully it also raises awareness of the copyright issues among all authors. Monitoring of the compliance with the open access policy falls under the responsibility of the faculty management. It is done through a web interface, Extramuep[1], where a spreadsheet detailing a specific year’s publications can be downloaded. One of the columns in the spreadsheet describes, among other things, whether or not that specific publication is in compliance with the open access policy. Our poster presentation will describe the submission process for a researcher the work processes of the library’s researcher support staff how compliance with the policy can be monitored by faculty management the experiences of the researcher support staff the result in the form of an increasing number of full text files in the repository The focus in this poster presentation is on how this implementation has changed the day-to-day work of the researcher support staff and the results in repository content quality.